2015
DOI: 10.1155/2015/971683
|View full text |Cite
|
Sign up to set email alerts
|

Associations of C1q/TNF-Related Protein-9 Levels in Serum and Epicardial Adipose Tissue with Coronary Atherosclerosis in Humans

Abstract: Objective. To investigate the correlation of CTRP9 with coronary atherosclerosis. Methods. Coronary angiography confirmed CAD in 241 patients (62 received CABG) and non-CAD in 121 (55 received valve replacement). Results. Serum levels of LDL-C, CRP, TNF-α, IL-6, and leptin in CAD patients were significantly higher than those in non-CAD patients (P < 0.05), but APN and CTRP9 were lower (P < 0.05). Serum levels of CTRP9 and APN were negatively related to BMI, HOMA-IR, TNF-α, IL-6, and leptin but positively to HD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 20 publications
4
41
0
Order By: Relevance
“…There is also a growing body of studies showing that CTRP1 and CTRP9 play a possible role in coronary artery disease and atherosclerosis [17,25,26]. In the present study we show that CTRP13 have a negative correlation with cIMT (as a marker for subclinical atherosclerosis), and CTRP13 also is a significant negative predictor of cIMT.…”
Section: Discussionsupporting
confidence: 68%
“…There is also a growing body of studies showing that CTRP1 and CTRP9 play a possible role in coronary artery disease and atherosclerosis [17,25,26]. In the present study we show that CTRP13 have a negative correlation with cIMT (as a marker for subclinical atherosclerosis), and CTRP13 also is a significant negative predictor of cIMT.…”
Section: Discussionsupporting
confidence: 68%
“…CTRP9 was shown to induce endothelium-dependent vasorelaxation [14], attenuate neointimal formation after vascular injury [13], and protect against cardiac injury [10, 11], and adverse cardiac remodeling [12] after acute infarction in mice. Consistent with those experimental studies, serum CTRP9 levels were found to be inversely related to obesity, insulin resistance, and dyslipidemia in a community-based population [15] and in patients with coronary artery disease [16]. In contrast, serum CTRP9 levels were positively associated with BMI in morbidly obese subjects requiring bariatric surgery [17] and with obesity, insulin resistance, and arterial stiffness in subjects with type 2 diabetes (T2D) [18].…”
Section: Introductionsupporting
confidence: 55%
“…Previous experimental studies in mice consistently demonstrated the beneficial effects of CTRP9 on vascular endothelial function [14], vascular smooth muscle cell proliferation [13], and the profile of inflammatory cytokines in macrophages [28, 29]. Several studies have investigated the association of CTRP9 with cardiovascular risk factors in human subjects [15, 16, 18], whereas only two reports have shown the association of CTRP9 with atherosclerosis [18] or cardiovascular disease [16]. In a study in which 35% of subjects had diabetes [16], the CTRP9 level in serum and epicardial adipose tissue negatively predicted the presence of coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations